An interview with Judith Kroll: The trajectory of studies in bilingual lexical access and directions for the future of research - Brentano, Luciana de Souza (2022)
This work is an interview carried out in California, with researcher and psycholinguist Judith Kroll, whose work is well respected around the world, in the field of Bilingualism and Cognition. Dr. Kroll tells us about her trajectory in researching bilingualism, as well as what we have already discovered about bilingual cognition, through studies conducted over the last 30 years. In addition, Dr. Kroll points out plausible directions for the continuity of future research in this area. Dr. Judith Kroll has several international awards as a researcher, and as such she runs a famous international research laboratory called Bilingualism, Mind, and Brain Lab at the University of California, in Irvine. This Fall 2021, I had the opportunity to participate as a visiting scholar at the University of California with Dr. Kroll, this brilliant researcher of bilingualism and cognition. My goal is to bring this knowledge to Brazil, to share it with professors and researchers in the area of ​​psycholinguistics of bilingualism.